ล่ามในฐานะผู้ช่วยนักข่าวต่างชาติ - สุญญาตา เมี้ยนละม้าย (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
This research aims to study the qualifications, roles and problems of interpreters as foreign journalist assistants. The scope of this study covers both staff and freelance Thai interpreters and English-speaking foreign journalists who have to work in countries where English is not mainly used such as Thailand and others. In-depth interviews were conducted with eleven foreign journalists, four staff interpreters and four freelance interpreters in six topics, namely recruitment of interpreters, desirable qualifacations of foreign journalist interpreters, considerations for hiring interpreters, roles of foreign journalist interpreters, ways to check the accuracy of interpreted messages and problems found in interpreter s performance. Results show that the recruiting system, the evaluation and the roles of interpreters are still unclear. However, the journalists and the interpreters share a lot of understanding and expectations. They report that desirable qualifications of interpreters are good language skills and journalistic experiences.The recruiting system of interpreters is by word of mouth. Many journalists do not have any specific measures to check the accuracy of interpreted messages. They tend to trust their interpreters despite the capability of cross checking. Nevertheless, a topic with conflicting opinions is regarding problems from interpreters performance. While interpreters are concerned about accuracy, journalists are worried about bias from interpreters